Perceptions Of Telehealth Among Healthcare Professionals During The Covid-19 Pandemic Era In X Hospital - Lyliana Endang Setianingsih (Sean Institute, 2023)
Telehealth is the delivery of health services, where patients and healthcare providers are separated by distance. Developments of information and communication technology have a very significant influence in every aspect of human life, one of which is in supporting the application of information and communication technology in the health sector, especially during the Covid-19 pandemic. X Hospital is located in Cikarang, is a type B private hospital. Most of the patients of X Hospital are BPJS patients, and according to the hospital administration, the percentage of BPJS patients can reach more than 80%. X Hospital was one of the Covid-19 referral hospitals in the Bekasi Regency area. The use of telehealth can improve patient care outcomes, mainly due to reduced time and costs for transportation and reduced barriers for patients to access to specialists. The purpose of the study was to get an overview of the effect of the Covid-19 pandemic on the perceptions of doctors and nurses in the use of telehealth at X Hospital. The method used for this research is qualitative method where data collection is done by interview about the perceptions of doctors and nurses in the use of telehealth at X Hospital. The results showed that the use of telehealth services at X Hospital was still limited to post Covid-19 patients and non-BPJS self-isolation patients. Most doctors have not supported the implementation of telehealth or telemedicine services for patients other than Covid-19 patients, due to obstacles in terms of medical ethics.